Circular RNAs in Human Cancer - Wang, Xiong; Li, Huijun; Lu, Yanjun; Cheng, Liming (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are a class of endogenous single-stranded covalently closed RNAs, primarily produced from pre-mRNAs via non-canonical back-splicing. circRNAs are highly conserved, stable, and expressed in tissue- and development-specific pattern. circRNAs play essential roles in physiological process as well as cancer biology. By the advances of deep sequencing and bioinformatics, the number of circRNAs have increased explosively. circRNAs function as miRNA/protein sponge, protein scaffold, protein recruitment, enhancer of protein function, as well as templates for translation involved in the regulation of transcription/splicing, translation, protein degradation, and pri-miRNA processing in human cancers and contributed to the pathogenesis of cancer. Numerous circRNAs may function in diverse manners. In this review, we survey the current understanding of circRNA functions in human cancer including miRNA sponge, circRNA-protein interaction, and circRNA-encoded protein, and summarize available databases for circRNA annotation and functional prediction.